PENGARUH TAX AMNESTY, PENGETAHUAN PERPAJAKAN, DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK - Sari, Viega Ayu Permata; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Tax revenue increases every year but it is not followed by the enhancement of tax ratio. It shows that taxrevenue has not optimal yet and there is tax potency which can be discovered by the government. One of theproblems which can obstruct optimum tax revenue is the taxpayer compliance. The purpose of this research ismeant to find out the influence of tax amnesty, tax knowledge, and tax authority service to the taxpayercompliance. This research is causality quantitative. The population is taxpayer, either individual taxpayers orcorporate taxpayers which are listed in Kantor Pelayanan Pajak (KPP) Pratama Surabaya Tegalsari. The samplehas been determined by using accidental sampling i.e. the collection of information from the taxpayers which isaccidentally met by researcher. 88 respondents have been obtained as samples. The data has been collected byissuing questionnaires and using likert scale 1 to 5. The data analysis technique has been done by using multiplelinear regressions and the SPSS program for windows. Based on the result of analysis, it shows that tax amnestyand tax knowledge gives positive influence. Meanwhile, tax authority service does not give any influence to thetaxpayer compliance.Keywords: Tax amnesty, taxation knowledge, tax authority service, obedience of tax payers.